The Role of the Millennial Generation in Developing Urban Farming as a Food Security Solution for Times of Crisis in Indonesia - Arvianti, Eri Yusnita; Setyabudi, Irawan; Novita, Retno Ayu Dewi (Universitas Panji Sakti, 2025)
This research analyses the role of millennials in the development of urban farming in Malang Regency, representing an area with high urban farming potential in Indonesia. Using a quantitative approach through an explanatory survey design, the study involved 210 millennial farmer respondents (aged 25-40) from 33 sub-districts in Malang Regency. Data was collected through a structured questionnaire with a 5-point Likert scale and analysed using PLS-SEM with WarpPLS 8.0. The model tests the relationship between five exogenous variables: Digital Technology Competency (X1), Entrepreneurial Ability (X2), Technical Knowledge (X3), Sustainability Awareness (X4), and Ecosystem Support (X5), and Local Food Resilience (Y), with Innovation Adoption (M) as a mediator. The main findings show the model is excellent (R² = 0.937) with all hypotheses significantly confirmed. Entrepreneurial ability has the strongest influence (β=0.42, p<0.05), followed by Digital Technology Competence and Ecosystem Support (β=0.36), Sustainability Awareness (β=0.31), and Technical Knowledge (β=0.25). Innovation adoption is proven to be an effective mediator, especially through Ecosystem Support (β=0.65, p<0.01). The research identified two innovative models: the NFT Vertical Hydroponic System and the IoT-based Smart Greenhouse Integrated Farming, which achieved 90% water efficiency and produced premium products. The significance of the research lies in its theoretical contribution regarding the role of millennials in food security and its practical implications for the development of national agricultural policy. The findings can be replicated in other urban areas of Indonesia with similar demographic and geographic characteristics, providing a blueprint for sustainable urban farming development to strengthen national food security.